Proceedings of the SIGCHI Conference on Human Factors in Computing Systems 2011
DOI: 10.1145/1978942.1979306
|View full text |Cite
|
Sign up to set email alerts
|

Enhancing physicality in touch interaction with programmable friction

Abstract: Touch interactions have refreshed some of the 'glowing enthusiasm' of thirty years ago for direct manipulation interfaces. However, today's touch technologies, whose interactions are supported by graphics, sounds or crude clicks, have a tactile sameness and gaps in usability. We use a Large Area Tactile Pattern Display (LATPaD) to examine design possibilities and outcomes when touch interactions are enhanced with variable surface friction. In a series of four studies, we first confirm that variable friction gi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
71
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
4
4
1

Relationship

1
8

Authors

Journals

citations
Cited by 127 publications
(72 citation statements)
references
References 35 publications
1
71
0
Order By: Relevance
“…Instead of creating vibrotactile stimulation on a user's finger, it suggests modifying friction between a sliding finger and the touch screen surface [2,11,29]. It has been demonstrated that such devices allow for the creation of not only a feasible and lightweight tactile feedback apparatus suitable for touch screens, but also provide rich, dynamic and highly satisfying user experiences [2].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Instead of creating vibrotactile stimulation on a user's finger, it suggests modifying friction between a sliding finger and the touch screen surface [2,11,29]. It has been demonstrated that such devices allow for the creation of not only a feasible and lightweight tactile feedback apparatus suitable for touch screens, but also provide rich, dynamic and highly satisfying user experiences [2].…”
Section: Introductionmentioning
confidence: 99%
“…Much of the previous work has focused on the hardware and materials required to build such tactile devices [1,2,29]. Levesque et al [10,11] used a squeeze-film effect to modulate the friction forces between the user's finger and a thin glass plate, where the level of force feedback was proportional to general mathematical functions, such as sinusoid profiles, and their spatial densities. It showed effective- Permission to make digital or hard copies of all or part of this work for personal or classroom use is granted without fee provided that copies are not made or distributed for profit or commercial advantage and that copies bear this notice and the full citation on the first page.…”
Section: Introductionmentioning
confidence: 99%
“…Some participants reported the texture having an impact of the interaction. Levesque et al [7] have used friction in a dynamic manner to improve target acquisition. Given the relatively low performance of the participants, it could be interesting to explore if tactile feedback could help controlling an indirect pointer.…”
Section: Discussionmentioning
confidence: 99%
“…Electrovibration can be perceived only when the user slides the finger over the surface. Another indirect stimulation technique that requires the user to move the finger over the surface to perceive a tactile sensation is based on ultrasound friction (squeeze-film effect) [20].…”
Section: Electrotactile and Electrovibration Stimulationmentioning
confidence: 99%